Plasma Hydrogen Sulfide Is Positively Associated With Post-operative Survival in Patients Undergoing Surgical Revascularization - Longchamp, Alban; MacArthur, Michael R.; Trocha, Kaspar; Ganahl, Janine; Mann, Charlotte G.; Kip, Peter; King, William W.; Sharma, Gaurav; Tao, Ming; Mitchell, Sarah J.; Ditrói, Tamás; Yang, Jie; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective. Hydrogen sulfide (H2S) is a gaseous signaling molecule and redox factor important for cardiovascular function. Deficiencies in its production or bioavailability are implicated in atherosclerotic disease. However, it is unknown if circulating H2S levels differ between vasculopaths and healthy individuals, and if so, whether H2S measurements can be used to predict surgical outcomes. Here, we examined: 1) Plasma H2S levels in patients undergoing vascular surgery and compared these to healthy controls, and 2) the association between H2S levels and mortality in a cohort of patients undergoing surgical revascularization. Methods. 115 patients undergoing carotid endarterectomy, open lower extremity revascularization or lower leg amputation were enrolled at a single institution. Peripheral blood was also collected from a matched control cohort of 20 patients without peripheral or coronary artery disease. Plasma H2S production capacity and sulfide concentration were measured using the lead acetate and monobromobimane methods, respectively. Results. Plasma H2S production capacity and plasma sulfide concentrations were reduced in patients with PAD (p<0.001, p=0.013 respectively). Patients that underwent surgical revascularization were divided into high versus low H2S production capacity groups by median split. Patients in the low H2S production group had increased probability of mortality (p=0.003). This association was robust to correction for potentially confounding variables using Cox proportional hazard models. Conclusion. Circulating H2S levels were lower in patients with atherosclerotic disease. Patients undergoing surgical revascularization with lower H2S production capacity, but not sulfide concentrations, had increased probability of mortality within 36 months post-surgery. This work provides insight on the role H2S plays as a diagnostic and potential therapeutic for cardiovascular disease.